Effect of hydro-priming and halo-priming on seed quality of faba bean varieties - ZEMET ALEMU CHANIE,; R.P.S. TOMER,; AMARE AYALE, (Seed Research, 2026)
Farmers and researchers have recognized that poor crop establishment is a major constaint for crop production. Effect of seed priming treatments an physiological seed quality and seed health of faba bean varieties was investigated. The experiment was laid out with priming treatment (i.e. unprimed, 6, 12, 18 and 24 hrs with water and with KH,PO, at 0.5% solution for 12 hrs) and faba bean varieties (i.e.CS20DK, Gachena and Moti) in CRD factorial arrangement with four replications. The laboratory and green house results field experiements revealed significant differences at (P